Pattern of Neuropsychiatric Illness in Children and Adolescent Presented in Psychiatry OPD of a Tertiary Care Hospital in North Lakhimpur District of Assam - Kristi Baruah; Bitupan Kalita; Pallab Kumar Bhattacharjee (National Journal of Medical Research)
Background: Understanding the neuropsychiatric morbidity among the children and adolescent is very essential for the promotion of mental and physical well- being. By looking into the patterns, magnitude of various neuropsychiatric illness among children and adolescents’ effective preventive and control strategies can be formulated. Considering all these perspectives the present study has been undertaken with the objective to assess the pattern of neuropsychiatric illness and also to assess the age, sex, religion, caste and locality of the in children and adolescents presented to psychiatry OPD of a tertiary care hospital in North Lakhimpur, Assam.